Pre-operative tomographic evaluation of calcaneum fractures in surgical planning - Castanho, Rafael Resende; Bordignon, Glaucia; Gomes dos Reis, Hélio Cezar (Scientific Journal of the Foot & Ankle, 2018)
Objective: To perform the correlation between the preoperative tomographic evaluation of patients with calcaneal fracture diagnosis and the access routes of choice, as well as the synthesis materials used. Methods: We reviewed 19 medical records of patients between 23 and 56 years old who underwent calcaneal fracture surgery from 01/01/2014 to 12/31/2015. We evaluated the mechanism of trauma, side, Essex-Lopresti classification, Böhler and Gissane angle in the pre- and postoperative period, Sanders tomographic classification and type of osteosynthesis performed. Angular measurements served as a reference for radiological analysis of the quality of the reduction. Results: 90% of the cases were of joint depression, the other 10% considered extra-articular. The preoperative Böhler angle varied between 5 and 40°, and between 10 and 38° in the postoperative period, and 55% of the fractures had an angular reconstruction considered good (between 20° and 40°). Gissane’s angle, on the other hand, varied between 110 and 170° in the preoperative period, and 102 and 132° in the postoperative period. In the tomographic analysis, Sanders IV classification was predominant (65%), followed by type IIIBC fractures (20%), and fractures type I, IIA and IIIAB (5% each). Osteosynthesis with plate and screw was the most used method (89.47%). Conclusion: Correct use of existing diagnostic imaging resources through radiographic and tomographic results provides the possibility of better preoperative planning in the intra-articular fractures of the calcaneus. However, in this study, there was no difference in the access route and synthesis according to the tomographic classification. Level of Evidence III; Diagnostic Studies; Study of Non-Consecutive Patients.